Hume's revenge. A defense of the moral emotivism (2017)
My porpose, in this paper, is to give a brief exposition of the Hume’s moral theory, and the positivist moral emotivism. I will present some of the strongest objections of both theories, which narrowly leave them out of combat. Finally, that the findings that give account of the functioning of the human moral nature, from a neuronal point of view, seem to fit the most basic presuppositions of both theories, without their compatibility being total. For this I will use an example: the murder of a subject and the subsequent statement of witnesses.